2020
DOI: 10.1051/e3sconf/202017212002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of monthly and daily profiles of DHW use in apartment blocks in Norway

Abstract: Profiles of domestic hot water (DHW) use give valuable information for achieving energy saving in buildings. In this article, analysis of monthly and hourly profiles in apartment blocks in Norway was performed. The aim was firstly to identify influencing factors on DHW use and afterwards to define typical DHW use profiles. Due to availability, two different data samples were used for monthly and hourly analysis. Monthly data from 49 apartments showed that approximately 30% of DHW was used in kitchens and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The daily values show an increased CHW during the morning, from about 06:00 during the weekdays and about during 08:00 weekends. There is a morning and afternoon peak, as also observed in other apartment buildings [24], but also the DHW uses during other daytime hours are quite high. An explanation for this could be that residents with small children or elderly are overrepresented, which is reasonable given that the apartments have two bedrooms only.…”
Section: Dhw Energy Need and Supplied Energysupporting
confidence: 54%
“…The daily values show an increased CHW during the morning, from about 06:00 during the weekdays and about during 08:00 weekends. There is a morning and afternoon peak, as also observed in other apartment buildings [24], but also the DHW uses during other daytime hours are quite high. An explanation for this could be that residents with small children or elderly are overrepresented, which is reasonable given that the apartments have two bedrooms only.…”
Section: Dhw Energy Need and Supplied Energysupporting
confidence: 54%
“…Both heating demand and electricity prices are influenced by the weather with higher energy prices often coinciding with higher heating demand such as in sustained cold periods. Real DHW profiles for Norwegian apartment buildings have been found to be less volatile than the standardised profile [60,61], which could result in smaller cost savings. However, the measured profiles also showed variation seasonally and between weekdays and weekends, which could offer other opportunities for load shifting.…”
Section: Discussionmentioning
confidence: 99%
“…The inaccuracy of profiles presented in the standards is one of the reasons for incorrect tank sizing. In the study [8], the DHW heat use profiles obtained from measurements in Norwegian residential buildings were compared with profiles presented in national and international standards. The comparison showed that the reference profiles in standards are not accurate enough.…”
Section: Introductionmentioning
confidence: 99%